Directed evolution of the 3-hydroxypropionic acid production pathway by engineering aldehyde dehydrogenase using a synthetic selection device - Seok, Joo Yeon; Yang, Jina; Choi, Sang Jin; Lim, Hyun Gyu; Choi, Un Jong; Kim, Kyung Jin; Park, Sunghoon; Yoo, Tae Hyeon; Jung, Gyoo Yeol (Metabolic Engineering, 2018)
3-Hydroxypropionic acid (3-HP) is an important platform chemical, and biological production of 3-HP from glycerol as a carbon source using glycerol dehydratase (GDHt) and aldehyde dehydrogenase (ALDH) has been revealed to be effective because it involves a relatively simple metabolic pathway and exhibits higher yield and productivity than other biosynthetic pathways. Despite the successful attempts of 3-HP production from glycerol, the biological process suffers from problems arising from low activity and inactivation of the two enzymes. To apply the directed evolutionary approach to engineer the 3-HP production system, we constructed a synthetic selection device using a 3-HP-responsive transcription factor and developed a selection approach for screening 3-HP-producing microorganisms. The method was applied to an ALDH library, specifically aldehyde-binding site library of alpha-ketoglutaric semialdehyde dehydrogenase (KGSADH). Only two serial cultures resulted in enrichment of strains showing increased 3-HP production, and an isolated KGSADH variant enzyme exhibited a 2.79-fold higher catalytic efficiency toward its aldehyde substrate than the wild-type one. This approach will provide the simple and efficient tool to engineer the pathway enzymes in metabolic engineering.
Keywords: 3-Hydroxypropionic acid; Aldehyde dehydrogenase; Biological production; Catalytic efficiencies; Directed evolution; Evolutionary approach; Semialdehyde dehydrogenase; Synthetic biology; Aldehyde Dehydrogenase; Directed Molecular Evolution; Escherichia coli; Escherichia coli Proteins; Lactic Acid; 3-hydroxypropionic acid; Directed evolution; Metabolic engineering; Screening; Synthetic biology; Transcription factor